What Drives Local Public Investments? Evidence from Poland - Monika Banaszewska (Institute of Economic Research (IER), 2017)
Local public investments satisfy basic local communities' needs and are crucial from the perspective of regional convergence. Against this background, investments by Polish local government pose as an interesting research subject. It is because, due to its size and dynamics, local public investments exert a considerably significant influence on the Polish economy. Self-government entities with primary responsibility for conducting local public investments in Poland are municipalities. The paper aims to identify fiscal, demographic and infrastructural determinants of municipal investment spending in Poland. I use panel data for 2412 Polish municipalities over the period 2007-2014. For institutional reasons, the sample excludes cities with county rights. The baseline specification employs two-way fixed-effects (FE) estimation that controls both for municipality and year fixed effects. To test for robustness, the sample is restricted to municipalities with up to 20,000; 10,000 and 5,000 inhabitants. For each considered sample there are four regression specifications implemented. Investment spending increases both in own revenues and grants. On the contrary, I document the negative impact of indebtedness level and the coverage of water supply and sewage systems. The coefficients on population size and the share of old inhabitants cease to be negative and statistically significant for municipalities with fewer than 10,000 inhabitants. The results indicate that, apart from fiscal capacity, the investment policies of Polish municipalities are affected by economies of scale, local communities' preferences and infrastructural endowment. The study also shows that incurring debt should be of particular concern for supervisory and control bodies.
Keywords: D78; H72; R53; 330; investment activity; municipal government; fiscal federalism